Sustainable Corporate Incubation to Create Innovative D2C Value Propositions - A Case Study - Jeremy Schönwälder; Anja Weber (Marketing Review St.Gallen, 2021)
Direct-to-consumer (D2C) marketing strategies commonly require large basket sizes to reach profitable growth. Thus, mass-market brands which offer low-price consumer packaged goods (CPG) face particular challenges when pursuing a D2C strategy. Creating a strong value proposition in the light of existing e-commerce platforms is far from trivial. Sustainable corporate incubation offers iterative routes to tackle D2C barriers for such brands. Based on a case study at Henkel, the largest CPG manufacturer in Germany, an explorative incubation approach to identify new ways of D2C business is proposed.
Keywords: 650